Pengembangan Produk Unggulan Daerah Berbasis Ekonomi Kreatif di Kota Bandung dan Kabupaten Badung - Sidauruk, Rosmawaty; Apriani, Tini; Hamudy, Moh Ilham A (Jurnal Bina Praja, 2019)
The government issued various regulations to support the development of a creative economy. However, the regulations had not provided a significant impact on the development of the creative economy product in the regions. This study observed the state of the creative economy’s Regional Best Products (Produk Unggulan Daerah/PUD), the effort to develop it and the obstacles to its development in the City of Bandung and Badung District. This study used a descriptive method with a qualitative approach. The data was collected using interviews, FGD, and documentation. The study showed that the development of the creative economy’s regional Best Products was not optimal This was due to the inability of the existing regulation to provide a significant impact, although the regional government conducted various development efforts in line with the capability of the region.